Real Exchange Rate Adjustment in and out of the Eurozone - Berka, Martin; Devereux, Michael B; Engel, Charles (American Economic Review, 2012)
It is often suggested that currency unions unduly inhibit the efficient adjustment of real exchange rates. Recently, this has been seen as a key failure of the Eurozone. This paper presents evidence that throws doubt on this conclusion. Our evidence suggests that real exchange rate movement within the Eurozone was at least as compatible with efficient adjustment as the behavior of real exchange rates for the floating rate countries outside the Eurozone. This interpretation is consistent with a model in which nominal exchange rate movements give rise to persistent deviations from the law of one price in traded goods.